2017
DOI: 10.4102/sajbm.v48i3.35
|View full text |Cite
|
Sign up to set email alerts
|

The influence of post-2008 legislation on an acquisition that turned hostile: A South African case study

Abstract: Hostile acquisitions have a significant impact on managers and employees. The possibility of an acquisition creates uncertainty and when the acquisition turns hostile it is even more disruptive to the target organisation. Also, negative perceptions are often created in the media about the acquirer that influence employees' attitudes in the target organisation. Processes to successfully integrate the acquirer and target organisations are impacted by these antagonistic pre-acquisition circumstances.The Companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The conflicting research incorporating an overall ESG score in both developed and developing markets is particularly interesting. Sayed (2018) had inconclusive findings, whilst Chetty et al (2014) and Erasmus et al (2019) found some positive relationships between ESG and firm performance and Biggs et al (2017) found negative relationships. A variety of methods to test the relationship, particularly in measuring ESG as a score with several metrics deemed suitable, for example, ROE or ROA (2018) utilised a variety of compliance-based approaches, whilst Du Toit & Lekoloane (2018) used news-based strategies.…”
Section: Developing Market Findingsmentioning
confidence: 99%
“…The conflicting research incorporating an overall ESG score in both developed and developing markets is particularly interesting. Sayed (2018) had inconclusive findings, whilst Chetty et al (2014) and Erasmus et al (2019) found some positive relationships between ESG and firm performance and Biggs et al (2017) found negative relationships. A variety of methods to test the relationship, particularly in measuring ESG as a score with several metrics deemed suitable, for example, ROE or ROA (2018) utilised a variety of compliance-based approaches, whilst Du Toit & Lekoloane (2018) used news-based strategies.…”
Section: Developing Market Findingsmentioning
confidence: 99%